Dpal ldan sa skya pa'i rgyun mkho'i chos spyod kyi rim pa khyer bde kun tshaṅ - Thub-bstan-snyan-grags (The Corporate Body of the Buddha Educational Foundation, 2002)
Collection of daily prayers from the Sakya order